Politics of ambivalent hospitality: Shifting positions toward International STEM students in U.S. federal policy - Kim, Judy (Journal of International Students, 2026)
In the United States, federal policies have long shaped the conditions under which international students in science, technology, engineering, and mathematics (STEM) are recruited and retained. Prior scholarship, however, has often portrayed these policies primarily as hostile to these students. In this critical integrative literature review, I examine how federal policies have positioned international STEM students from the post–World War II era to the 2020s. Drawing on a post/decolonial lens, I synthesize scholarship alongside policy documents and enrollment data. The analysis reveals an evolving politics of ambivalent hospitality: federal policies welcome international STEM students for their scientific contributions while simultaneously casting them as potential threats. These findings call for historically informed support systems at both institutional and policy levels that recognize the conditional and uneven nature of federal openness.